A novel host-responsive sensor mediates virulence and type III secretion during Pseudomonas aeruginosa-host cell interactions - O'Callaghan, J.; Reen, F.; Adams, C.; Casey, P.; Gahan, C.; O'Gara, Fergal (Society for General Microbiology, 2012)
Sensitive sensory mechanisms are instrumental in affording Pseudomonas aeruginosa the capacity to establish diverse yet severe human infections, which can manifest themselves in long-term untreatable disease. The ability of P. aeruginosa to tightly regulate gene expression and virulence factor production, in response to activation of these sensory components, enables the pathogen to sustain infection despite the host immune response and aggressive antibiotic treatment. Although a number of factors are recognized as playing a role in early infection, very little is known regarding the sensors involved in this process. In this study, we identified P. aeruginosa PA3191 as a novel host-responsive sensor that plays a key role during P. aeruginosa–host interactions and is required for optimum colonization and dissemination in a mouse model of infection. We demonstrated that PA3191 contributed to modulation of the type III secretion system (T3SS) in response to host cells and T3SS-inducing conditions in vitro. PA3191 (designated GtrS) acted in concert with the response regulator GltR to regulate the OprB transport system and subsequently carbon metabolism. Through this signal transduction pathway, T3SS activation was mediated via the RsmAYZ regulatory cascade and involved the global anaerobic response regulator Anr.